Safety of lixisenatide plus basal insulin treatment regimen in Indian people with type 2 diabetes mellitus during Ramadan fast: A post hoc analysis of the LixiRam randomized trial. (May 2020) - Sahay, Rakesh; Hafidh, Khadijah; Djaballah, Khier; Coudert, Mathieu; Azar, Sami; Shehadeh, Naim; Hanif, Wasim; Hassanein, Mohamed
Abstract: Aims: Hypoglycemia is one of the most important complications associated with Ramadan fasting in people with type 2 diabetes. LixiRam (NCT02941367) was the first randomized trial comparing safety and efficacy of lixisenatide + basal insulin (BI) vs. sulphonylurea + BI in people with type 2 diabetes who fast during Ramadan. This post hoc analysis focuses on the LixiRam study population from India. Methods: Adults with type 2 diabetes insufficiently controlled with sulphonylurea + BI ± another oral anti-hyperglycemic drug were randomized 1:1 to receive lixisenatide + BI or to continue sulphonylurea + BI treatment. Results: In total, 150 participants were randomized in India. One participant (1.3%) with lixisenatide + BI vs. 5 participants (6.8%) with sulphonylurea + BI experienced ≥1 documented symptomatic hypoglycemic event during the Ramadan fast (odds ratio [OR]: 0.22; 95% confidence interval [CI]: 0.02–1.93). Incidence of any hypoglycemia was numerically lower with lixisenatide + BI vs. sulphonylurea + BI during Ramadan fasting (1.3% [1/75] vs. 14.7% [11/75], respectively; OR: 0.09; 95% CI: 0.01–0.69). No new safety signals were identified. Conclusions: A combination of lixisenatide prandial GLP1-RA + BI may be a suitable treatment option for people with type 2 diabetes who elect to fast during Ramadan. Clinical Trial Registry: clinicaltrials.gov (NCT02941367).